Diálogos Palimpsésticos: Jorge Luis Borges, Miguel De Cervantes E Pierre Menard - Pereira, Maria De Jesus Rodrigues [UNIFESP] (2018)
The Aim Of The Article Is To Create Transtextual Dialogues Between Writer Miguel De Cervantes And Jorge Luis Borges. Despite Of Significant Time And Cultural Distance Between The Authors It Is Possible To Observe That Both Established Intense Relationships With Different Literary Works, In Order To Break With Current Traditions In Their Respective Periods And, For That Reason, Propose Reformulations Way Of Writing.The Study Begins With Don Quixote De La Mancha, A Novel Written By Miguel De Cervantes In 1605 And The Short Story Pierre Menard, Author Of Don Quixote Published In 1939 By Jorge Luis Borges. Cervantes Does Not Employ Intertextuality As A Resource To Adopt A Cultured And Erudite Man Perspective But Uses It To Compose His Reproaches Of This Common Practice For Men Of Fine Arts And Especially The Novels Of Chivalry. Borges Composes His Literary Enigmas Thanks To The Intertextual Practice And The Intense Relations That He Establishes With Different Types Of Texts. Not Surprisingly, The Argentinian Auth